Remittances and Economic Stability in El Salvador: Trends from 2000 to 2020 - José Alberto M. Calderón; Ana Beatriz H. Castillo (Studies in Social Science & Humanities, 2025)
Remittances have emerged as a cornerstone of El Salvador’s economy, significantly contributing to household income, poverty reduction, and macroeconomic stability. Between 2000 and 2020, remittance inflows grew steadily, accounting for nearly 20% of GDP by 2020. This paper explores the historical trends and macroeconomic implications of remittances, emphasizing their role in addressing key economic challenges and fostering community investments in education, healthcare, and housing. However, the analysis also highlights potential risks of remittance dependence, including labor market distortions and vulnerability to external economic shocks. Policy recommendations focus on leveraging remittances for sustainable development while reducing reliance on external financial inflows through diversification and local economic strengthening.